PENGARUH LATIHAN OPERAN LARI MENYILANG TERHADAP KEMAMPUAN CHEST PASS BOLA BASKET TIM PUTRA BHINNEKA BASKETBALL CLUB PEKANBARU - Chandra, David; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is conducted to find out if there is any effect of crossing run pass training on basketball chest pass ability on Bhinneka Basketball Club Pekanbaru team, so that when doing chest pass technique can be done well and maximal. The form of this research is by experimental research, with basketball player population of Bhinneka Basketball Club Pekanbaru, the sample in this study is the entire population of 12 people. Instrument used in this research is AAHPERD Basketball Passing Test, to measure the skill of chest pass accurately in the moving state. After that, the data were treated with statistics, for normality with liliefors test at the level of α (0.05). The hypothesis proposed is the effect of cross pass exercise on the ability of the pass chest. Based on the statistical data analysis, the result obtained L_count smaller than the L_table, then the data distributed normal. Based on test result t calculate T_count 5.77 and T_table of 1.79 means T_count > T_tabel. And therefore, there is the effect of cross run pass practice on the ability of a basketball chest pass on the team male of bhinneka basketball club pekanbaru.Key word : cross pass training, chest pass, AAHPERD Basketball Passig Test